2021
DOI: 10.1186/s13019-021-01736-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intraoperative dexmedetomidine on cognitive dysfunction after surgery: a updated meta-analysis

Abstract: Background Postoperative cognitive dysfunction (POCD) is one of the most common. Neuroprotective effects of dexmedetomidine (DEX) are reported in previous studies but evidence regarding the POCD is still unclear. In order to gain latest evidence, the present study analyzes the outcomes of randomized controlled trials (RCTs) which utilized DEX with general anaesthesia perioperatively. Method Four online databases (PubMed, Embase, the Cochrane Librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Third, as for the limitations of the included studies or the review process itself, our included studies have heterogeneities such as different cognitive evaluation tools (Lili et al, 2013;Xu et al, 2017;Zhang et al, 2019;Zhu et al, 2016). Different neurocognitive evaluation tools may have different cognitive evaluation results (Li et al, 2021a;Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, as for the limitations of the included studies or the review process itself, our included studies have heterogeneities such as different cognitive evaluation tools (Lili et al, 2013;Xu et al, 2017;Zhang et al, 2019;Zhu et al, 2016). Different neurocognitive evaluation tools may have different cognitive evaluation results (Li et al, 2021a;Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Since the incidence of POCD was signif-icantly different between cardiac surgery and noncardiac surgery, we only evaluated the prevention and treatment effects of these drugs on POCD in noncardiac surgery (Brodier & Cibelli, 2021;Czok et al, 2021). We found that neurocognitive tests are often performed on postoperative days 1, 3, and 7, according to the present RCTs (Duan et al, 2021;Huang et al, 2020a;Li et al, 2021a;Mansouri et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The most common perioperative complication of primary cleft palate repair is respiratory in nature, 16 representing a potentially useful context for DEX utilization. DEX has been shown to ameliorate postoperative cognitive dysfunction 17 and be more effective 1308…”
Section: Discussionmentioning
confidence: 99%
“…The most common perioperative complication of primary cleft palate repair is respiratory in nature, 16 representing a potentially useful context for DEX utilization. DEX has been shown to ameliorate postoperative cognitive dysfunction 17 and be more effective than propofol in treating emergence delirium in the postanesthetic stage of pediatric patients. 18 It has also been associated with lower pain scores, decreased opiate use, and shorter hospital LOS in children who underwent decompression of a Chiari malformation.…”
Section: Discussionmentioning
confidence: 99%